Дія економічних законів в теорії людського потенціалу - Яковенко, Р. В.; Yakovenko, R. (Кіровоград : „Поліграф-сервіс”, 2010)
Розкриваються нові закономірності перебігу економічних процесів, які визначаються наявними змінами в людині, виробництві та суспільстві. На основі положень теорії людського потенціалу визначено основні закономірності процесів виробництва, споживання та обігу товарів і доходів. The new laws of the course of economic processes, which are determined by the existing changes in man, industry and society, are revealed. Based on the provisions of the theory of human potential, the main regularities of the processes of production, consumption and circulation of goods and income are determined.
Effect of economic laws in the theory of human potential
Keywords: людський потенціал; закон вартості; закон Сея; закон економії часу; закон зростання потреб; the human potential; the law of value; the law of Say; the law of time saving; the law of growth needs